(untitled) (Raparin Journal of Humanities (RJH), 2024)
The purpose of this study is to analyze the role of the ability of auditors to use accounting software in reducing audit risk, because accounting software is one of the most important tools that various companies and factories use in their business and is of great importance is Various operations in the audit process and their impact on risk. This is because auditors’ inability to handle these plans affects audit risk because the results of these plans are not properly audited. To achieve the research objectives, the statistical program SPSS was used and a questionnaire was created and distributed to a sample of examiners in the Iraqi Kurdistan region. After collecting and analyzing the data, the two researchers came to a number of conclusions, the most important of which are: Using accounting software in mathematical operations requires the auditor’s expertise, awareness and ability to handle different types of these procedures. In light of the results of the research, the researchers concluded a set of recommendations, the most important of which is to increase qualification courses for auditors and the necessity of working to issue legislation or laws requiring the use of computer programs.